Applications of differential Scanning Calorimetry in developing cryopreservation strategies for Parkia speciosa - Nadarajan, Jayanthi; Mansor, M; Krishnapillay, B; Staines, H; Benson, E; Harding, K (MTT, 2008)
Shoot-tips of Parkia speciosa, a recalcitrant seed producing tropical leguminous tree withstood cryopreservation using encapsulation-vitrification in combination with trehalose preculture. Differential Scanning Calorimetry (DSC) revealed that trehalose moderated the thermal characteristics of the shoot-tips. A 30 min PVS2 treatment had the lowest glass transition temperature (Tg) (-50.21 ± 1.07ºC) when applied in combination with 5% (w/v) trehalose. The Tg increased to -40.22 ± 0.95ºC as the sugar s concentration was decreased to 2.5% (w/v). Tg heat capacity for shoot-tips treated with 2.5% and 5% (w/v) trehalose and exposed to PVS2 for 30 min increased from 0.17 ± 0.05 to 0.23 ± 0.01 J.g-1 respectively. Enthalpies of the melt-endotherm varied in proportion to trehalose concentration, for the 30 min PVS2 treatment, whereas the melt enthalpy for control shoots was >150 J.g-1 and decreased to ca. 60 J.g-1 with 2.5% (w/v) trehalose. For 5% and 10% (w/v) trehalose treatments, enthalpy declined to ca. 24 and 12 J.g-1 respectively and freezing points were depressed to 75ºC and 85ºC with 2.5% and 5% trehalose (w/v), respectively. DSC elucidated the critical points at which vitrification occurred in germplasm exposed to trehalose and PVS2. A 60 min PVS2 treatment supporting ca. 70% survival was found optimal for stable glass formation during cooling and on rewarming.
Keywords: Ka; differential scanning calorimetry; Parkia speciosa; trehalose; vitrification